A Survey of Parthian Military Architecture - Farrokh, Kaveh (Tools of war, 2023)
This article provides a synopsis of Parthian military architecture by an initial examination of Arsacid military requirements for the defence of their empire. Following an overview of Central Asian circular systems, Parthian architectural innovations, Seleucid-Hellenic influences, and the tripartite system, Parthian military architecture in the empire’s northeast and Central Asian territories (Margiana, Hyrcania, Aria, Bactria), Iran and the Persian Gulf, Mesopotamia and Syria are analysed. The article concludes with a discussion of possible defensive wall systems during the Parthian era.